PENGARUH DIMENSI EKUITAS MEREK TERHADAP MINAT BELI PADA KERTANEGARA GUEST HOUSE MALANG - Wardani, Ervan Ade (Department of Management, 2015)
Intention this research is to test dimension of equity brand have an effect to enthusiasm buy at Guest House Kertanegara Malang and to test brand equity influence to enthusiasm buy at Guest House. Population in this research are guest using service of Guest House Kertanegara, by using technique of convenience purposive sampling. Sample size 100 respondents. Technique analysis is linear regression analysis by using test of regression doubled linear. The result of research show that linear regression analysis is positive relationshio between the brand equity and enthusiasm., test t test and f test, indicating that brand equity have influence of significant to enthusiasm buy. Between awareness brand, brand association, perception of quality, dimension brand and loyality owning most influence significan is awareness of brand, brand association, perception of quality of, and brand loyality.